EFFECTS OF ACUTE HYPOXIA ON INTRACELLULAR-pH REGULATION IN ASTROCYTES CULTURED FROM RAT HIPPOCAMPUS - Bevensee, Mark O. (2007)
We used the pH-sensitive dye BCECF to evaluate the effect of acute (5-10 min) hypoxia (∼3% O(2)) on the regulation of intracellular pH (pH(i)) in astrocyte populations cultured from rat hippocampus. For cells in the nominal absence of CO(2)/ [Formula: see text] at an extracellular pH of 7.40 (37°C), acute hypoxia caused a small (0.05) decrease in steady-state pH(i), but increased the pH(i)-recovery rate from an acid load during all but the late phase of the pH(i) recovery. During such pH(i) recoveries, the total acid-extrusion rate (φ(E), the product of dpH(i)/dt and proton buffering power) decreased with increasing pH(i). Hypoxia alkali shifted the plot of φ(E) vs. pH(i); over the upper ∼85% of the φ(E) range, this shift was 0.15-0.30. Hypoxia also stimulated the pH(i)-recovery rate from an alkali load. Under normoxic conditions, switching the extracellular buffer to 5% CO(2)/22 mM [Formula: see text] also alkali shifted the φ(E)-pH(i) plot (upper ∼85%) by 0.4-0.5. Superimposing hypoxia on CO(2)/ [Formula: see text] further alkali shifted the φ(E)-pH(i) plot (upper ∼85% of the φ(E) range) by 0.05-0.15. The SITS-insensitive component of φ(E) was alkali shifted by 0.20-0.30, whereas the SITS-sensitive component of φ(E) was depressed in the low pH(i) range. Thus, in the nominal absence of CO(2)/ [Formula: see text] , acute hypoxia has little effect on steady-state pH(i) but stimulates acid extrusion and acid loading, whereas in the presence of CO(2)/ [Formula: see text] , hypoxia stimulates the SITS-insensitive but inhibits the SITS-sensitive acid extrusion.